Tempo de retorno à deambulação de cães paraplégicos sem dor profunda submetidos à cirurgia descompressiva e fisioterapia no pós-operatório - Rodrigues, Carolina Francisca Girardon (2023)
The objective of this retrospective study was to evaluate the time to return to ambulation in paraplegic dogs without deep pain affected by intervertebral disc extrusion (IVED) and treated with decompressive surgery associated or not with physiotherapy in the postoperative period (PO). Paraplegic dogs without nociception (deep pain) lasting up to 96 hours, with a definitive diagnosis of thoracolumbar EDIV, were included. Thirty-four animals were divided into two groups; 22 (GI) for those who underwent decompressive surgery and physiotherapy in the PO and 12 (GII) for dogs that did not undergo any therapeutic modality after surgery. The therapeutic modalities used were cryotherapy, massage, stretching, passive movement of the joint, stimulation of the flexor reflex, brushing the foot pads, standing weight bearing, neuromuscular electrical stimulation (ENNM) and transcutaneous electrical stimulation (TENS). The time to return to ambulation was shorter in GI for those who recovered motor function (p=0.04), whose median was 90 days compared to 225 days in GII. Based on the findings of this study, it is concluded that physiotherapy applied in the postoperative period reduces the time for returning to ambulation in paraplegic dogs without nociception surgically treated due to EDIV.